Water quality effect on the Valle de Guadalupe aquifer in the agricultural soils salinity - Salgado Tránsito, Jorge Arturo; Palacios Vélez, Oscar; Galvis Spínola, Arturo; Gavi Reyes, Francisco; Mejía Sáenz, Enrique (Revista Mexicana de Ciencias Agrícolas, 2018)
InordertodeterminetheeffectofwaterqualityintheValle de Guadalupe aquifer, Baja California, Mexico, in the agricultural soils salinity the pH, electrical conductivity, total dissolved solids and the concentration of major ions in water of 66 wells were measured, from 754 that were in operation in the aquifer during 2009. The pH, electrical conductivity, carbonate, bicarbonate, chloride, sulfate, boron, phosphorus, nitrate, calcium, magnesium, sodium, potassium, and ammonium were analyzed in the paste extract saturation of the soil samples. 74% of the soils studied presented an amount higher than 15 mg kg-1 of nitrate, and due to sandy soils, contamination problems are attributed to nitrogen fertilizer applications. Water salinity is present throughout Valle de Guadalupe aquifer (classified as C3 and C4 in 85.9%), but soil salinity (pHmean= 7.6) is not present in the total area of the valley, so the aquifer water is not the only cause of the problem, water management for irrigation and fertilizer application should be studied to quantify their contribution to the soild salinity.
Keywords: chemical analysis; wells; irrigation